2001
DOI: 10.1002/cb.60
|View full text |Cite
|
Sign up to set email alerts
|

Salesperson characteristics affecting consumer complaint responses

Abstract: The important relationship between consumer complaint behaviour and brand and store loyalty is well established. The range of factors that favourably in¯uence the outcomes of complaining have received relatively less research attention. Therefore, this study tests the effects of two salesperson source characteristics: willingness to listen and product/store knowledge, on consumer complaint-related perceptions and intentions in a retail setting. Mall shoppers participated in a consumer complaint experiment to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
35
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 32 publications
3
35
0
2
Order By: Relevance
“…Research findings further indicate that the money spent on product development and promotion is often negated by the poor performance of salespeople in store (Clopton et al, 2001).…”
Section: Introduction and Motivation For The Studymentioning
confidence: 92%
See 3 more Smart Citations
“…Research findings further indicate that the money spent on product development and promotion is often negated by the poor performance of salespeople in store (Clopton et al, 2001).…”
Section: Introduction and Motivation For The Studymentioning
confidence: 92%
“…Goff et al (1997) found that salespeople's behaviour with respect to selling orientation-customer orientation (SOCO) significantly influences customers' satisfaction with the salesperson, dealer, product as well as the manufacturers and it has been found that consumers frequently recall and complain about bad experiences with salespeople (Morris, 2002:28). "Relationship retailing" with an emphasis on maintaining good relationships with customers is thus recommended (Clopton et al, 2001). Saxby (2003:4) is even more explicit in his summation that the very existence of many retailers depends on their sales personnel who actually represent their employers (retailers) in their interaction with consumers.…”
Section: The Multiple Roles Of a Salespersonmentioning
confidence: 99%
See 2 more Smart Citations
“…, 불평의 성공가능성 (Cho, 2000;Singh, 1990), 제품의 특성 및 중요성 (Baek & Lee, 2009;Folkes, 1984;Richins, 1983), 인구통계학적 특징이 나 상황적인 특성 (Clopton et al, 2001;Huh & You, 2001;Singh & Wilke, 1991 지의 가치유형으로 구분되고 있는 것으로 나타났다 (Yea, 2010;Kim, 2009;Park, 2008;Lee, 2008 (Mitchell, 1999;Riche, 1989). 또한 소비자가 가지고 있는 사회활 Frederick et al, 1988).…”
unclassified